A new species in the newly recorded genus Trachyusa (Hymenoptera: Braconidae: Alysiinae) from China - Yao, Junli; Kula, Robert R.; Chen, Jiahua (Zootaxa, 2015)
Trachyusa whartoni Yao sp. nov. from Dalian, Liaoning, China is described and illustrated. Trachyusa is a newly recorded genus in China. A key to the species of Trachyusa is provided based on the keys of Belokobylskij (1998), Papp (1967), and van Achterberg and O'Connor (1990). Type specimens of the new species are deposited in the Beneficial Insects Institute, Fujian Agriculture and Forestry University, Fuzhou, China.